Expanding LGBTQ+ Inclusivity: An Ecological Model of School Library Practice in Addition to Collection Development - Mohanty, Smita; Sahoo, Suchitra; Dhal, Shraddha; Swain, Sukanta Chandra (Indian Journal of Information Sources and Services, 2024)
This research explores the critical need for a holistic approach to LGBTQ+ inclusivity in school library services, moving beyond the traditional focus on collection development to address underexplored areas such as cataloguing practices, purchasing procedures, programming, policies, and community outreach. The school libraries often become a place of social stigma for LGBTQ+ students, and availability of fewer resources and institutional biases typically discourage them from accessing information and support from such libraries. For this purpose, this study will carry out research using a qualitative research design with the help of content analysis and case studies to identify the best practices and policies of selected school libraries in regard to addressing such matters. It sets much importance on cataloguing in such a way so that these LGBTQ+ resources, materials, etc. should be visible and accessible besides discussing budget limitations and community force behind acquiring the LGBTQ+ resources as a part of the library collection. This also emphasizes the requirement of an LGBTQ+ inclusive program with efficient community outreach that builds safe spaces for the student population LGBTQ+. The study further stresses the need for library policies and how librarians can become great advocates of LGBTQ+ rights and representation. A careful consideration of any aspect of library services described in this paper will help guide principles for making school libraries more inclusive and equitable. The implications are considered crucial for future research and practice, toward further development of library services to support the needs of LGBTQ+ students completely, which will enhance their well-being and academic success.